PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA WORDWALL TERHADAP AKTIVITAS BELAJAR PADA MATA PELAJARAN PENDIDIKAN PANCASILAi KELAS IViDI SD GUGUSiVI KECAMATANiSAWAN - Komang Juli Ardiani; IG. Agung Jaya Suryawan; Putu Yulia Angga Dewi (Widyajaya: Jurnal Pendidikan Guru Sekolah Dasar, 2026)
This paper strives to see the effect of the TGT model assisted by Wordwall media on the learning activities of fourth grade students in Pancasila Education subjects. Pancasila learning in elementary school is often considered boring, thus reducing student learning activities. Observations at SD Gugus VI Sawan District displayed that the average student the learning task was only 67.85. This research implemented an experimental approach supported by quantitative data. As well as with the type of pretest-posttest control group design. The sample of the study was class IV at SD Negeri 4 Sangsit with 36 students selected for the experimental class while class IV students at SD Negeri 1 Kerobokan with 37 students selected as the control class. Data gathering in this research employed observation, interviews, surveys, and document analysis explain the mean N-Gain value in the experimental class obtained 0.7119 with high class criteria. Then the mean N-Gain value in the control class was obtained 0.5206 with the criteria of the medium group, so the mean N-Gain value of the experimental class was greater than the mean N-Gain value the non-experimental group. Through the results of data analysis, the research explains that there is a significant difference in the learning activities Pupils taught via the Teams Games Tournament (TGT) approach assisted by wordwall media employed for students who were not instructed using the Teams Games Tournament (TGT) method, aided by wordwal tools in the Pancasila education map of grade IV students in SD Gugus VI Sawan sub-district seen from the t-count value of 10,496> t-table 1,667.